2012
DOI: 10.1111/j.1600-0625.2011.01412.x
|View full text |Cite
|
Sign up to set email alerts
|

IL‐17 downregulates filaggrin and affects keratinocyte expression of genes associated with cellular adhesion

Abstract: Atopic eczema and psoriasis are common skin diseases. While it is well established that the pathogenesis of these diseases varies, both are characterized by impairment in epidermal barrier function and abnormal IL-17 expression in the skin and peripheral blood. Recent findings indicated that filaggrin is essential during barrier formation and its insufficiency underlies the pathogenesis of atopic eczema. Filaggrin downregulation has also been reported in psoriasis. It is clear that Th1 ⁄ Th2 bias influences ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
137
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(154 citation statements)
references
References 80 publications
8
137
1
8
Order By: Relevance
“…Numerous studies have demonstrated that several inflammatory mediators (e.g., IL4, IL13, IL25, IL17A and histamine) affect keratinocyte differentiation, most often leading to impaired barrier formation. [72][73][74][75] Studies on noncutaneous epithelium have established that inflammatory mediators are involved in TJ assembly and disassembly during inflammatory conditions, 76 and also in keratinocytes an influence of several cytokines on TJ proteins/function was described (see below). Whether these mediators directly affect epidermal TJs or whether it is an indirect effect via altered differentiation is an active area of research.…”
Section: Tj and Adaptive Immune Barriermentioning
confidence: 99%
“…Numerous studies have demonstrated that several inflammatory mediators (e.g., IL4, IL13, IL25, IL17A and histamine) affect keratinocyte differentiation, most often leading to impaired barrier formation. [72][73][74][75] Studies on noncutaneous epithelium have established that inflammatory mediators are involved in TJ assembly and disassembly during inflammatory conditions, 76 and also in keratinocytes an influence of several cytokines on TJ proteins/function was described (see below). Whether these mediators directly affect epidermal TJs or whether it is an indirect effect via altered differentiation is an active area of research.…”
Section: Tj and Adaptive Immune Barriermentioning
confidence: 99%
“…1 and Supplementary Fig. S1) [16][17][18][19][20]30 . In agreement, we find that IL-17A interferes with differentiation and alters gene expression, which is completely blocked by Secukinumab (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly effective in the treatment of severe plaque psoriasis and psoriatic arthritis 14,15 . Expression studies revealed that IL-17 controls genes that encode for proteins associated with differentiation, with anti-microbial defense and with immune cell recruitment and activation, including filaggrin, S100A7, DEFB4, CCL20, and IL-8 (CXCL8) 16,17 . Many of these genes were confirmed when gene expression of psoriatic skin lesions was compared with control samples [18][19][20] .…”
mentioning
confidence: 99%
“…75 Por outro lado, a IL-17 suprime a expressão de filagrina e de genes envolvidos na adesão dos queratinócitos, parecendo contribuir para a disrupção da barreira cutânea nas doenças inflamatórias da Revista Científica da Ordem dos Médicos www.actamedicaportuguesa.com pele. 76 Os efeitos da IL-17 estendem-se a outros tipos celulares cutâneos além dos queratinócitos, como as células dendríticas mielóides, os macrófagos, os fibroblastos ou as células endoteliais, potenciando as características inflamatórias observadas na psoríase.…”
Section: O Tratamento Da Psoríase Visando a Il-17unclassified